Поточечная оценка комонотонного приближения - Дзюбенко, Г.А. (Український математичний журнал, 1994)
Доведено, що для неперервної на [- 1; 1 ] функції f(x) з обмеженою кількістю проміжків незростання і неспадання існує послідовність многочленів Pn(x), локально монотонних так само, як f(x) і |f(x)−Pn(x)|≤Cω₂(f;n⁻²+n⁻¹(√1−x²) , C — стала, яка залежить від довжини найменшого проміжку. We prove that, for a continuous functionf(x) defined on the interval [−1,1] and having finitely many intervals where it is either nonincreasing or nondecreasing, one can always find a sequence of polynomialsP n (x) with the same local properties of monotonicity as the functionf(x) and such that ¦f(x)−P n (x) ¦≤Cω₂(f;n⁻²+n⁻¹√1−x²), whereC is a constant that depends on the length of the smallest interval.